PELANGGARAN KEDAULATAN NEGARA TERKAIT TINDAKAN SPIONASE DALAM HUBUNGAN DIPLOMASI INTERNASIONAL - Kutha Giri Putra, Ngakan Kompiang; Sudiarta, I Ketut (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 03, Mei 2014)
In the diplomatic relations between States, it has been generally developed the mechanism for collecting information legally through official diplomatic channel, in order to support the national interest of each State. But, secretly gathering the information is considered as a violation against the sovereignty of a State. The practice of espionage is a term used to describe the act of collecting information secretly in an international relations. International Law has actually prohibited any State for doing practice of espionage against other countries. Besides classified as an intervention to the sovereignty of the State, such action also violates the principle of cooperative relations based on good faith.
Keywords: Diplomacy, Sovereignty, State, Espionage